El impacto del burnout en las cuidadoras de personas con discapacidad usuarias del Centro de Salud 3 de la ciudad de Loja, primer trimestre del año 2023 - Peralta Hidalgo, Magali Alexandra (2023)
The objective of this study is to analyze the impact of burnout in caregivers of people with disabilities who attend Health Center 3 in the city of Loja. Interviews were conducted with the caregivers and the results report that caregivers of people with disabilities have a profile characterized by being women who are family members of the people under their care, and who present high levels of emotional exhaustion and low personal fulfillment. That is why it is pertinent to study this impact that is being experienced in our society due to the workload of many workers, in a general opinion is that, if workers are having a bad day, then that is their personal problem, it is not an important concern for the organization. In addition, in the present research, clear and precise objectives are set out, such as the theoretical basis of the impact of burnout, the identification of causes and effects, and finally the design of specific strategies that contribute to the prevention and management of burnout syndrome in caregivers of people with disabilities. Therefore, the methodology used in this research project is qualitative, because through the use of interviews it was possible to demonstrate the impact of burnout on the respondents, who were the users of Health Center 3. It is concluded that overload and Burnout syndrome in family caregivers were found to be average. The factor related to overload and Burnout was the daily time dedicated to caregiving. Based on the results, it is proposed to establish preventive training programs about caregiving aimed at family caregivers with disabilities; in order to contribute to the well-being of caregivers.